2005
DOI: 10.1074/jbc.m502780200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein-tyrosine Phosphatase 1B in Integrin Signaling

Abstract: Protein-tyrosine phosphatase 1B (PTP1B) is a key negative regulator of insulin and leptin signaling and a novel therapeutic target for the treatment of type 2 diabetes, obesity, and other associated metabolic syndromes. Because PTP1B regulates multiple signal pathways and it can both enhance and antagonize a cellular event, it is important to establish the physiological relevance of PTP1B in these processes. In this study, we utilize potent and selective PTP1B inhibitors to delineate the role of PTP1B in integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 56 publications
4
79
0
Order By: Relevance
“…27 Remarkably, the positive role of PTP1B in cell motility was frequently associated with the stimulation of integrin-dependent signaling. 3,4,12,17,18,22 In contrast, the negative effect of PTP1B on cell motility was related to antagonizing signaling from growth factor receptor tyrosine kinases. [24][25][26][27] In a recent quantitative study, we analyzed the intrinsic motility and migration parameters of PTP1B-null cells (KO cells) in an isotropic 2-D fibronectin substratum.…”
Section: Long-range Impact Of Ptp1b On Cell Adhesion and Motilitymentioning
confidence: 88%
See 2 more Smart Citations
“…27 Remarkably, the positive role of PTP1B in cell motility was frequently associated with the stimulation of integrin-dependent signaling. 3,4,12,17,18,22 In contrast, the negative effect of PTP1B on cell motility was related to antagonizing signaling from growth factor receptor tyrosine kinases. [24][25][26][27] In a recent quantitative study, we analyzed the intrinsic motility and migration parameters of PTP1B-null cells (KO cells) in an isotropic 2-D fibronectin substratum.…”
Section: Long-range Impact Of Ptp1b On Cell Adhesion and Motilitymentioning
confidence: 88%
“…17 Src activation by PTP1B was further demonstrated in several different cell models. 3,4,12,18,[45][46][47] Using a combination of time lapse, total internal reflection fluorescence microscopy, and BiFC we were able to visualize ER-bound PTP1B/ Src complexes as small fluorescent puncta distributed uniformly at the plasma membrane in contact with the substrate. 8 The substrate trap mutation (D181A) in PTP1B and the tyrosine 529 at the C-tail of Src were both required for BiFC to occur, as well as the plasma membrane targeting motif of Src.…”
Section: Ptp1b Regulation Of Cell-matrix-dependent Signaling To Rho Gmentioning
confidence: 99%
See 1 more Smart Citation
“…It is involved in leptin and insulin signaling and in several other signaling pathways such as growth factor and integrin mediated processes. 57 Several studies demonstrated that changes in abundance and distribution of PTPases could impair insulin signal transduction, causing insulin resistance. 58 Aberrant insulin signaling, which leads to insulin resistance, hyperinsulinaemia and increased concentrations of endogenous estrogen and androgen, was linked to high breast cancer risk by clinical and experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TC-PTP and PTP-1B dephosphorylate similar but largely distinct sets of non-RTK substrates. For example, PTP-1B targets include the Src family kinases (SFKs) (8,13,43) and JAK2 (14,28,49,80), whereas TC-PTP targets the SFKs (71) and JAK1 (60). These observations point to the fact that, despite their high similarity between their PTP domains, PTP-1B and TC-PTP can target different substrates.…”
Section: Ptp-1b and Tc-ptp: Close Cousins But Definitely Not Twinsmentioning
confidence: 82%